2004
DOI: 10.4049/jimmunol.173.7.4377
|View full text |Cite
|
Sign up to set email alerts
|

Direct Antigen Presentation by a Xenograft Induces Immunity Independently of Secondary Lymphoid Organs

Abstract: The location of immune activation is controversial during acute allograft rejection and unknown in xenotransplantation. To determine where immune activation to a xenograft occurs, we examined whether splenectomized alymphoplastic mice that possess no secondary lymphoid organs can reject porcine skin xenografts. Our results show that these mice rejected their xenografts, in a T cell-dependent fashion, at the same tempo as wild-type recipients, demonstrating that xenograft rejection is not critically dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
0
20
1
Order By: Relevance
“…Mouse experimental models provide accumulating evidence that adaptive immunity can be initiated independent of secondary lymphoid organs. For instance, splenectomized alymphoplastic mice can reject xenografts (Tesar et al, 2004), clear viral infection with the development of primary and secondary immune responses (MoyronQuiroz et al, 2004(MoyronQuiroz et al, , 2006 or mount an allergic airway inflammation after inhalation of allergens (Gajewska et al, 2001). However, our results lead to the hypothesis that tertiary lymphoid structures adjacent to tumors could function as primary sites for the generation of antitumor adaptive immune reactions.…”
Section: Immune Infiltration In Human Tumorscontrasting
confidence: 49%
“…Mouse experimental models provide accumulating evidence that adaptive immunity can be initiated independent of secondary lymphoid organs. For instance, splenectomized alymphoplastic mice can reject xenografts (Tesar et al, 2004), clear viral infection with the development of primary and secondary immune responses (MoyronQuiroz et al, 2004(MoyronQuiroz et al, , 2006 or mount an allergic airway inflammation after inhalation of allergens (Gajewska et al, 2001). However, our results lead to the hypothesis that tertiary lymphoid structures adjacent to tumors could function as primary sites for the generation of antitumor adaptive immune reactions.…”
Section: Immune Infiltration In Human Tumorscontrasting
confidence: 49%
“…In this context, it has been reported that extranodal lymphoid structures may participate in the induction of specific immune responses 55,56 . Considering that TLS contain high number of antigen-presenting DCs 40 , the possible occurrence of an intratumoral cancer-specific T-cell priming (in addition to the conventional priming occurring in SLO) could influence the evolution of the tumour and therefore the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Yu and colleagues have shown that the priming of naïve T cells in the tumor leads to the eradication of established tumors [76] which argues for the crucial role of local immunological microenvironment. In different mouse models (allergy, transplantation, melanoma), cumulative data report the participation of ectopic lymphoid structures in the initiation of immune responses [77][78][79]. Interestingly, Randall et al demonstrated that the induction of BALT correlated with robust primary cellular and humoral responses to influenza virus in mice which do not contain any secondary lymphoid organs [77][78][79].…”
Section: Lung Tumor Cells Exhibit a Differential Response To Stimulatmentioning
confidence: 98%